THE IMPACT OF FINANCIAL DISTRESS, CLIENT FIRM SIZE, AND AUDIT TENURE ON AUDITOR SWITCHING IN HEALTHCARE COMPANIES LISTED ON THE IDX PERIOD 2019-2023 - Situmeang, Melinda Sharon; Rinendy, Jhon; Ferinia, Rolyana (JEA17: Jurnal Ekonomi Akuntansi, 2024)
In the corporate sector, it is normal practice to transfer auditors in order to achieve financial statement transparency. The goal of this research is to examine how auditor switching in healthcare businesses listed on the IDX during the 2019–2023 timeframe is impacted by financial distress, client firm size, and audit tenure. 50 samples were gathered from 10 businesses that satisfied the research criteria using purposive sampling and secondary data. The findings of the binary logistic regression analysis indicate that, in part, there is no connection exists among auditor switching and financial distress, client firm size, audit tenure. However, when taken into consideration all at once, auditor switching is influenced by financial distress, client firm size, and audit tenure